A novel phosphoramide compound, DCZ0847, displays in vitro and in vivo anti-myeloma activity, alone or in combination with bortezomib. (28th May 2020) - Chen, Gege; Hu, Ke; Sun, Haiguo; Zhou, Jinfeng; Song, Dongliang; Xu, Zhijian; Gao, Lu; Lu, Ye; Cheng, Yao; Feng, Qilin; Zhang, Hui; Wang, Yingcong; et al.
Abstract: Multiple myeloma (MM) is an incurable hematological malignancy, for which novel effective therapies are urgently needed. We synthesized a novel phosphoramide compound, DCZ0847, showing a potent anti-myeloma activity both in vitro and in vivo . DCZ0847 showed high cytotoxicity towards primary MM cells but had no effect on normal cells and was well tolerated in vivo . The anti-myeloma activity of DCZ0847 was associated with inhibition of cell proliferation; promotion of cell apoptosis via mitochondrial transmembrane potential collapse and caspase-mediated extrinsic or intrinsic apoptotic pathways; and the induction of G2/M phase arrest via downregulation of CDC25C, CDK1, and cyclin B1. In particular, DCZ0847 induced DNA damage and triggered a DNA-damage response by enhancing the levels of γ-H2A.X, phosphorylated (p)-ATM, p-ATR, p-Chk1, and p-Chk2. Additionally, DCZ0847 was able to overcome the bone marrow stromal cells-induced proliferation of MM cells and blocked JAK2/STAT3 signaling. Importantly, DCZ0847 acted synergistically with bortezomib, with the combination exerting greater cytotoxic effects in vitro and in vivo . Together, our results indicate that DCZ0847, alone or in combination with bortezomib, may represent a potential new therapy for patients with MM. Highlights: DCZ0847 had high cytotoxicity in primary MM cells but did not affect normal cells. DCZ0847 had a synergistic effect with bortezomib and was well tolerated in vivo . DCZ0847 inhibited MM proliferation, promoted apoptosis and triggered G2 M phase arrest. DCZ0847 induced DNA damage and triggered a DNA damage response. DCZ0847 reversed the cytoprotective effects of BMM and blocked JAK2/STAT3 signaling.